Toll-Like Receptor Signaling Drives Btk-Mediated Autoimmune Disease - Rip, Jasper; de Bruijn, Marjolein J. W.; Appelman, Marjolein K.; Pal Singh, Simar; Hendriks, Rudi W.; Corneth, Odilia B. J. (Frontiers in Immunology, 2019)
Bruton's tyrosine kinase (Btk) is a signaling molecule involved in development and activation of B cells through B-cell receptor (BCR) and Toll-like receptor (TLR) signaling. We have previously shown that transgenic mice that overexpress human Btk under the control of the CD19 promoter (CD19-hBtk) display spontaneous germinal center formation, increased cytokine production, anti-nuclear autoantibodies (ANAs), and systemic autoimsmune disease upon aging. As TLR and BCR signaling are both implicated in autoimmunity, we studied their impact on splenic B cells. Using phosphoflow cytometry, we observed that phosphorylation of ribosomal protein S6, a downstream Akt target, was increased in CD19-hBtk B cells following BCR stimulation or combined BCR/TLR stimulation, when compared with wild-type (WT) B cells. The CD19-hBtk transgene enhanced BCR-induced B cell survival and proliferation, but had an opposite effect following TLR9 or combined BCR/TLR9 stimulation. Although the expression of TLR9 was reduced in CD19-hBtk B cells compared to WT B cells, a synergistic effect of TLR9 and BCR stimulation on the induction of CD25 and CD80 was observed in CD19-hBtk B cells. In splenic follicular (Fol) and marginal zone (MZ) B cells from aging CD19-hBtk mice BCR signaling stimulated in vitro IL-10 production in synergy with TLR4 and particularly TLR9 stimulation, but not with TLR3 and TLR7. The enhanced capacity of CD19-hBtk Fol B cells to produce the pro-inflammatory cytokines IFNγ and IL-6 compared with WT B cells was however not further increased following in vitro BCR or TLR9 stimulation. Finally, we used crosses with mice deficient for the TLR-associated molecule myeloid differentiation primary response 88 (MyD88) to show that TLR signaling was crucial for spontaneous formation of germinal centers, increased IFNγ, and IL-6 production by B cells and anti-nuclear autoantibody induction in CD19-hBtk mice. Taken together, we conclude that high Btk expression does not only increase B cell survival following BCR stimulation, but also renders B cells more sensitive to TLR stimulation, resulting in increased expression of CD80, and IL-10 in activated B cells. Although BCR-TLR interplay is complex, our findings show that both signaling pathways are crucial for the development of pathology in a Btk-dependent model for systemic autoimmune disease.